Enabling human–machine collaboration in infrastructure inspections through mixed reality. (August 2022) - Al-Sabbag, Zaid Abbas; Yeum, Chul Min; Narasimhan, Sriram
Abstract: In this study, we propose a novel end-to-end system called Human–Machine Collaborative Inspection (HMCI) to enable collaboration between inspectors with Mixed Reality (MR) headsets and a robotic data collection platform (robot) for structural inspections. We utilize the MR headset's holographic display and precise head tracking to allow inspectors to visualize and localize information (e.g., structural defect) on the real scenes, which are gathered by the robot and processed by an offsite computational server. The primary use case of HMCI is to enable the inspector to visualize, supervise, and improve results produced by automated defect detection algorithms in near real-time. The workflow in HMCI starts with collecting images and depth data to generate 3D maps of the site from the robot. A technique called single-shot localization is developed to create visual anchors for real-time spatial alignment between the robot and the MR headset. The 3D map and images are then sent to the computational server for analysis to detect defects and their locations. Then, the information is received by the MR headset and overlaid on the actual scenes to visualize it with spatial context. An experimental study is conducted in a lab environment to demonstrate HMCI using Microsoft HoloLens 2 (HL2) as the MR headset and Turtlebot2 as the robot. We start with the reconstruction of a 3D environment using a 3D depth sensor (Azure Kinect) on Turtlebot2 and visually detect fiducial markers as regions-of-interest (replicating structural damage) along a predefined inspection path. Then, regions-of-interest are successfully anchored to the real scene and visualized through HL2. To our knowledge, HMCI is one of the first human–machine collaborative systems that can integrate robots and inspectors with the MR headset, which has been developed, tested, and presented for structural inspection.